Sulfidogenic treatment of acid mine drainage using anaerobic membrane bioreactor - Yurtsever, Adem; Şahinkaya, Erkan; İşler, Ece; Çoban, Işık (Elsevier, 2019)
The study aims at evaluating the robustness of sulfidogenic anaerobic membrane bioreactor for the treatment of synthetic acid mine drainage (pH similar to 4.0) containing Fe, Cu, Zn, Co, Mn, Ni and As. The performance of the anaerobic membrane bioreactor was evaluated at varying fluxes (3.6-8.25 l(m(2)h)(-1)), hydraulic retention times (1.3-2 days), gas scouring rates (1.67-7.8 m(3)-gas (m(2)h)(-1)) and heavy metal concentrations. Anaerobic membrane bioreactor was operated at sulfate and chemical oxygen demand concentrations of 2000 mg l(-1 )and 1500 mg l(-1), respectively, corresponding to chemical oxygen demand/sulfate ratio of 0.75. Ethanol was externally supplemented as carbon and energy sources for sulfate-reducing bacteria. The performance improved with doubling metal concentrations in the feed as both sulfate reduction and chemical oxygen demand oxidation performances reached 95%. Electron flow from ethanol oxidation to sulfate reduction averaged 90%. Alkalinity generated from sulfate reduction increased the feed pH from 4.0 to neutral values. Throughout the study over 99% removals were observed for Fe, Cu, Zn, Co, and Ni. Whereas partial removals of Mn (76-91%) and As (41-67%) were observed.
Keywords: Anaerobic membrane bioreactor; Acid mine drainage; Arsenic removal; Sulfate reduction